The impact of prenatal group B streptococcus screening as a national health policy in Taiwan - Fung-Wei Chang; Chun-I Lee; Hueng-Chuen Fan; Her-Young Su; Yung-Liang Liu; Cheng-Yu Chen (Elsevier, 2017)
Objective: There was no national data on group B streptococcus (GBS) infections in Taiwan. Until 2012, when prenatal GBS screening was introduced to obstetric practices as a national health policy aimed at reducing neonatal GBS infections. The purpose of this study was to examine the impact of this national health policy on the incidence of maternal GBS colonization and neonatal GBS infection rate. Relatedly, the clinical characteristics of neonatal GBS infection were investigated to determine the correlations between the incidence of maternal GBS colonization and the neonatal GBS infection rate. Materials and methods: This population-based nationwide study used data for 2012-2013 from the National Health Insurance Research Database of Taiwan. A total of 789 newly diagnosed pregnant women with genital GBS infection were recruited. Results: The maternal GBS screening rate was 93.2%. The maternal colonization rate of GBS was around 8.2%, and the incidence of neonatal GBS infection was 22.6%. The data indicate that no sepsis was developed in any of the cases, while fever was found in 3 cases (3/179, 1.7%) and UTI was found in 1 case (1/179, 0.6%). Conclusions: We conclude that a policy calling for universal maternal rectovaginal cultures for GBS with intrapartum antibiotic prophylaxis is a good national policy for reducing morbidity due to GBS infections in neonates in Taiwan.